Estimation of Temperature Influence on Creep Rate of High-Temperature Elements in Steam Turbines and Steam Pipelines - A. G. Gerasimova; E. N. Kriksina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper considers a high temperature influence on strength characteristics of steam pipelines and steam turbine parts of high and medium pressure. The charts showing a decisive temperature importance in diffuse creep have been presented in the paper. The paper contains a calculation of steel self-diffusion coefficient. Dependence Dsd = f(t) for more accurate assessment of  resource characteristics of the applied steel has been proposed in the paper.